HUBUNGAN ANTARA ASPEK PSIKOSOSIAL DENGAN KELELAHAN MULTIDIMENSI AKIBAT KERJA PADA PEKERJA MIGAS PT.X SELAMA PENDEMI COVID-19: Hubungan Antara Aspek Psikososial Dengan Kelelahan Multidimensi Akibat Kerja Pada Pekerja Migas PT.X Selama Pendemi Covid-19 - Makhrus Shofi; Dadan Erwandi (Universitas Pahlawan, 2022)
The relationship between fatigue and psychosocial aspects in the upstream oil and gas industry is still relatively not widely studied. Since end of 2019, there have been several policies related to the COVID-19 pandemic, which impact to the psychological aspects of the workers in response to those unexpected changing situations. The aim of this study was to determine the relationship between psychosocial aspects and the multidimensional work-related fatigue both onshore and offshore upstream oil and gas during the 2020-2021 Covid-19 pandemic. This study is a quantitative analytic study with a cross sectional study design. This study was conducted at one of the upstream oil and gas in East Kalimantan, Indonesia. Psychosocial aspects were measured by using the 3rd Version of Copenhagen Psychosocial Questionnaire (COPSOQ III) questionnaire, whilst work-related fatigue was measured by using the Multidimensional Fatigue Inventory-20 (MFI-20). Multivariable Linear Regression analysis was used to examine the associations and interactions. The result of study revealed all satisfaction subscales of psychosocial aspects were perceived as good (high level) by workers. Meanwhile dissatisfaction subscales were at medium level during the COVID-19 pandemic. The work-related fatigue tended to be at low level. After the confounding variables were controlled, the Recognition, Job Satisfaction and Work Life Conflict aspects were found to have association with total fatigue in Onshore, whereas the job satisfaction is the only psychosocial aspect that is related to the total fatigue in offshore area. Company is encouraged to concentrate the future fatigue prevention programs particularly on reducing the Work Life Conflicts and developing proactive measures which may improve the meaning of satisfaction at work. Keywords : COPSOQ, MFI-20, Fatigue, Psychosocial, COVID-19, Upstream Oil and Gas